Effectiveness of Oral Herbal in Postpartum and Breastfeeding - Sayuti, Nutrisia Aquariushinta; Atikah, Nur (Poltekkes Kemenkes Surakarta, 2024)
Background: Health care during the postpartum and breastfeeding periods fulfils the needs of the mother and baby. 'Jamu', or herbal medicine, is often used for this purpose, but there needs to be more evidence of its effectiveness. The public's insufficient understanding of herbal medicine necessitates a systematic review to assess its contents, benefits, and side effects. The systematic review aimed to examine oral herbal medicines during puerperium or breastfeeding, using the RCT method to provide evidence of IB levels in EBM. Methods: Inclusion criteria were articles in randomised controlled trials (RCTs) to investigate the effectiveness of oral herbs during the puerperium and lactation. The methodological quality of articles was tested with the Jadad Score. Results: The five (5) selected articles have good quality (the Jadad Score was 5–8). The study tested five herbs, including fenugreek, honey, bitter fennel, Brazilian propolis, barley malt, and Thai herbal tea